SARCINA VENTRICULI IN THE STOMACH: AN UNEXPECTED AND POTENTIALLY DANGEROUS VISITOR: SARCINA VENTRICULI EN ESTÓMAGO: UN VISITANTE INESPERADO Y POTENCIALMENTE PELIGROSO - Gordillo de la Fuente, Hellen Johanna (2024)
ABSTRACT Introduction: Sarcina ventriculi is a Gram (+), anaerobic, non-motile cocci, with a fermentative carbohydrate metabolism, that survives and grows without problems in environments with acidic pH. It is a known etiological agent in veterinary pathology, however its pathogenic role in humans is controversial. In recent years, the finding of this microorganism in different anatomical places has been reported in humans with increasing frequency, predominantly in the upper digestive tract, mainly in the stomach, in patients with dyspepsia and/or delayed gastric emptying, some of these cases with serious evolution, even fatal. Clinical case: we report the case of a patient with dyspeptic symptoms, whose gastric biopsy identified Sarcina ventriculi and whose targeted pharmacological treatment ended the discomfort described. To the best of our knowledge, this is the first case reported in Peru. Keywords: Sarcina ventriculi, dyspepsia, gastritis (Source: MeSH – NLM)